High accuracy potentiostat with wide dynamic range and linearity - Toprak, Serdar; Vural, Revna Acar; Batur, Okan Zafer (ELSEVIER GMBH, 2021)
Electrochemical measurement require potentiostat to ensure the operational stability during the sensing and conversion of the sensor signals. This article presents a potentiostat circuit with high linearity and accuracy bidirectional current readout circuit for a wide dynamic current range. A current conveyor circuit with a wide current range from +/- 50 nA to +/- 400 mu A is constructed by combining a low-noise current mirror based OTA and a regulated current mirror employing accurate and linear output characteristics. The potentiostat is designed in 0.18 mu m TSMC technology with +/- 0.9 V nominal power supply, and the results obtained are based on simulation and performed with Cadence (TM) tools. The potentiostat circuit achieves a minimum detectable current of 1 nA within current range of +/- 400 mu A. The detectable current range is 112 dB with R-2 linearity of 0.999999993 and maximum error of 1.3%. The input referred noise of the current conveyor is 24.48 fA/root Hz@1 kHz, and integrated referred noise is 0.912 pA within 0.01 Hz - 1 kHz bandwidth. The static power consumption of the potentiostat circuit is 1.993 mW. The control amplifier and the current readout circuit consume 1.98 mW and 13 mu W, respectively. The proposed circuit is capable of providing low noise and high accuracy current measurement with low power consumption and highly linear output characteristics.
Keywords: Potentiostat; Bidirectional current conveyor; CMOS integrated circuit design; Voltammetry; ELECTROCHEMICAL SENSORS; DESIGN; NOISE; Engineering; Telecommunications